Context as other minds : the pragmatics of sociality, cognition, and communication - Givón, Talmy, 1936- (John Benjamins Pub., 2005)
"Givon's new book re-casts pragmatics, and most conspicuously the pragmatics of sociality and communication, in neuro-cognitive, bio-adaptive, evolutionary terms. The fact that context, the core notion of pragmatics, is a framing operation undertaken on the fly through judgements of relevance, has been well known since Aristotle, Kant and Peirce. But the context that is relevant to the pragmatics of sociality and communication is a highly specific mental operation - the mental modeling of the interlocutor's current, rapidly shifting belief-and-intention states. The construed context of social interaction and communications is thus a mental representation of other minds."--Jacket